Whole-body and hand-arm vibration in in-house transport - KOWALSKI, Piotr; ZAJĄC, Jacek (Archives of Acoustics, 2010)
A dynamic economy contributes to the increase in the number of workers exposed to mechanical vibration caused by machines and transport equipment. As the means of transport are insufficiently recognised sources of mechanical vibrations, this article presents the results of whole-body and hand-arm vibration tests of 30 most common means of in-house transport. An analysis of vibration signals recorded at each workstation according to PN-EN 14253 and PN-EN ISO 5349 made it possible to determine the weighted values of components of directional vibration acceleration and the values of daily vibration exposure A(8). In order to assess exposure to whole-body and hand-arm vibration at the tested workstations of in-house transport, indices of vibration hazard related to admissible values, the total evaluation index (developed in a previous study at CIOP-PIB) and a three-degrees scale for assessing exposure to vibrations were used. The assessment showed that the workstations were a major hazard. Vibration hazards at all those workstations were classified as either medium or high.